Humanizing LIS education and practice : diversity by design - Dali, Keren; Caidi, Nadia (Abingdon, Oxon : Routledge, 2021)
Humanizing LIS Education and Practice: Diversity by Design demonstrates that diversity concerns are relevant to all and need to be approached in a systematic way. Developing the Diversity by Design concept articulated by Dali and Caidi in 2017, the book promotes the notion of the diversity mindset. Grouped into three parts, the chapters within this volume have been written by an international team of seasoned academics and practitioners who make diversity integral to their professional and scholarly activities. Building on the Diversity by Design approach, the book presents case studies with practice models for two primary audiences: LIS educators and LIS practitioners. Chapters cover a range of issues, including, but not limited to, academic promotion and tenure; the decolonization of LIS education; engaging Indigenous and multicultural communities; librarians' professional development in diversity and social justice; and the decolonization of library access practices and policies. As a collection, the book illustrates a systems-thinking approach to fostering diversity and inclusion in LIS, integrating it by design into the LIS curriculum and professional practice. Calling on individuals, organizations, policymakers, and LIS educators to make diversity integral to their daily activities and curriculum, Humanizing LIS Education and Practice: Diversity by Design will be of interest to anyone engaged in research and professional practice in Library and Information Science.
Chapter 8 Professional development in diversity, equity, and inclusion: From add-on to "separate, but equal" to Diversity by Design -- Introduction -- The diversity problem -- Professional development in academic librarianship -- Two models of DEI professional development programming -- Diversity as "add-on" -- Diversity as "separate, but equal" -- A Diversity by Design approach to DEI -- Conclusion -- References -- Chapter 9 Library publishing for an inclusive education -- Introduction -- Interpretation of diversity -- Transformation in the post-colonial era -- Social justice
OCLC-licensed vendor bibliographic record.
Keywords: Libraries and minorities; Minorities in library science; Library education; LANGUAGE ARTS & DISCIPLINES / Library & Information Science